Functional Outcome Evaluation of Grade III Open Tibial Fracture Treated by External Fixation as Definitive Treatment - Soetjahjo, Bintang; Ermawan, Rieva; Saputra, Rhyan Darma; Hancoro, Udi Herunefi; Nugroho, Bagus Jati; Anugra, Jiva Yori (Indonesian Journal of Medicine, 2021)
Background: Tibial shaft fractures including open tibial fractures grade III are one of the most common fractures of long bones. There are many methods of conservative and operative treatment, one of them is external fixation. External fixation is more common used temporary in polytraumatized patients with tibial shaft fractures. The study was undertaken to see if the patient can be treated with external fixation as the definitive treatment and evaluate the functional outcome after the treatment.Subjects and Method: A retrospective review of a prospectively-collected database was performed. Data was taken from the Orthopaedic Department of RSUD Dr. Moewardi Hospital patients’ database. The study included all patients who underwent grade III open tibial fracture treatment from May 2018 to May 2019. A total of 8 patients who were included in our study were a patient with open tibial fractures grade III planned for external fixaton as definitive treatment. They were evaluated radiographically and clinically to determine the union rate. The data were reported descriptively.Results: External fixator time ranged in this study around 240 days. In this study, there were a few patients whose progress were remain unknown due to loss of contact. Fractures studied 5 out of 8, no patient were union after 8 months of external fixator used. 4 out of 8 patients were reported non-union after 8 months based on their radiological examination (50%) and 1 out of 8 patients were reported has been performed Removal of External Fixation (ROEF) after 5 months of treatment. The rest of the 3 patients’ results were remain unknown.Conclusion: Open tibial fractures grade III  of the leg can be managed with use of external fixator as a definitive treatment. However, the use of external fixation does not provide maximum results in grade III A tibial fractures.Keywords: open tibial fractures, external fixation, union, malunionCorrespondence: Bintang Soetjahjo. Dr. Moewardi General Hospital. Jl. Kolonel Sutarto 132, Jebres, Surakarta, Central Java, Indonesia. 57126. Email: bjortho@yahoo.com. Indonesian Journal of Medicine (2021), 06(04): 452-459https://doi.org/10.26911/theijmed.2021.06.04.11